Evaluation of cell disruption for partial isolation of intracellular pyruvate decarboxylase enzyme by silver nanoparticles method - J. Tangtua; C. Techapun; R. Pratanaphon; A. Kuntiya; V. Sanguanchaipaiwong; T. Chaiyaso; P. Hanmuangjai; P. Seesuriyachan; N. Leksawasdi; N. Leksawasdi (My University, 2015)
Candida tropicalis TISTR 5350 was used in the comparison of seven concentration levels of silver nanoparticles (0, 5, 10, 15, 20, 25, and 30 μg ml –1 ) for cell disruption methods. The optimized cell disruption strategy was selected based on the optimal protein yield and biological activity. The maximum volumetric and specific pyruvate decarboxylase (PDC, EC 4.1.1.1) activities (0.53±0.05 U ml –1 and 0.17±0.02 U mg –1 protein, respectively) were observed at 15 μg ml –1 silver nanoparticles. The silver nanoparticle concentration level of 15 μg ml–1 was investigated further by comparing the reaction mixtures at different time intervals of 0, 1, 2, 3, 4, 5, and 6 min. The result showed that the highest specific PDC activity of 0.39±0.01 U mg –1 protein was obtained from mixing for 3 min. This was not significantly different (P≤0.05) from other mixing time intervals.
Keywords: Silver nanoparticle; Specific activity; Pyruvate decarboxylase; Biochemical Acid Research Studies